A função da vergonha na constituição da subjetividade em Freud: visando estabelecer as aproximações e as distinções. - Santos, Jonatas Tiburtino dos (2017)
The present study has as its research theme the function of the shame in the constitution of the subjectivity and in nowadays culture, and it questions the consequences of its decline in the present days. To approach such a theme we theoretically thought about the points from which Sigmund Freud and Jacques Lacan present approaches and distinctions about the function of shame in the constitution of the subjectivity. Aiming to achieve such an objective a bibliographic review of the concept of shame in Freud’s work was made for the purpose of – effectively – detect the role that was given in the constitution of the subjectivity; the consequences of its decline in the subjectivities were investigated and what is its role in the malaise nowadays, according to the Lacanian view; the approaching points and the distinctions between Sigmund Freud’s work and Jacques Lacan’s teaching about the function of shame in its constitution were pointed out. Such research found, in Freud’s work, that the shame favors the constitution of the subjectivity and takes part in the formation of the mechanisms that specify the neurotic processes. In the Lacanian teaching, the master significant degeneracies as the alteration that precedes and, in the scope of the affections, caused the decline of shame, whose consequences tell about the transformations in a relationship of the subject with the law, and the enjoyment, besides its gradual clearance related to the significants of the Great Other.